Analisis Keterbukaan Informasi Publik di Era Digital pada Museum Brawijaya Malang - Narocha Mihasu Aisya; Shohib Muslim (INDO PUBLISHING, 2025)
The development of digital technology has brought significant changes in the way people access and share information. Public information transparency is crucial, especially in institutions such as the Brawijaya Museum, which functions as a repository of historical and cultural heritage. However, problems arise when access to information in this museum is still limited, both physically and digitally, making it difficult for the public to obtain the necessary data.. This study aims to evaluate the extent to which the Brawijaya Museum applies the principle of public information transparency in the digital era, as well as to identify the challenges and opportunities faced in providing transparent and accountable access to information. This study employed a qualitative descriptive method. In-depth interviews were done with museum managers and visitors to obtain diverse perspectives. Additionaly, direct observation was also conducted to scrutinize the information transparency practices implemented in the museum. The data analysis was done qualitatively. The results of the study showed that the Brawijaya Museum did not fully implement the principle of public information transparency. Information available through social media tended to be limited to visiting activities, without providing in-depth context regarding the museum's collections and history. The use of social media, such as Instagram and WhatsApp, was still less than optimal, with minimal socialization among the public about the existence of these platforms. In addition, the absence of clear regulations in information management hampered the effectiveness of information accessibility for the public, creating a gap in public participation. The conclusion of this study is that the Brawijaya Museum needs to increase the openness of public information by developing a more comprehensive digital platform, such as an official website. Suggestions given include the need for active socialization regarding existing social media, as well as the development of more in-depth and educational content by implementing an e-catalog product of previously created photo archive collections. It is also hoped that these steps will enable the museum to expand its outreach and boost public engagement in its events.